Surface expression of the immunotherapeutic target GD2 in osteosarcoma depends on cell confluency. Issue 5 (2nd April 2021) - Wiebel, Malena; Kailayangiri, Sareetha; Altvater, Bianca; Meltzer, Jutta; Grobe, Kay; Kupich, Sabine; Rossig, Claudia
Abstract: Background: Chimeric antigen receptor (CAR) T‐cell therapy of pediatric sarcomas is challenged by the paucity of targetable cell surface antigens. A candidate target in osteosarcoma (OS) is the ganglioside GD2, but heterogeneous expression of GD2 limits its value. Aim: We aimed to identify mechanisms that upregulate GD2 target expression in OS. Methods and results: GD2 surface expression in OS cells, studied by flow cytometry, was found to vary both among and within individual OS cell lines. Pharmacological approaches, including inhibition of the histone methyltransferase Enhancer of Zeste Homolog 2 (EZH2) and modulation of the protein kinase C, failed to increase GD2 expression. Instead, cell confluency was found to be associated with higher GD2 expression levels both in monolayer cultures and in tumor spheroids. The sensitivity of OS cells to targeting by GD2 ‐specific CAR T cells was compared in an in vitro cytotoxicity assay. Higher cell confluencies enhanced the sensitivity of OS cells to GD2 ‐antigen specific, CAR T‐cell‐mediated in vitro cytolysis. Mechanistic studies revealed that confluency‐dependent upregulation of GD2 expression in OS cells is mediated by increased de novo biosynthesis, through a yet unknown mechanism. Conclusion: Expression of GD2 in OS cell lines is highly variable and associated with increasing cell confluency in vitro. Strategies for selective upregulation of GD2 are needed to enable effective therapeutic targeting of this antigen in OS.